Bacteriological Profiles of Semen Culture in Male Patients Having Primary Infertility, Attending Mombasa Assisted Reproduction Centre - Thanki, Uday Dineshchandra; Waithaka, Stanley King'e; Suleiman, Mbaruk Abdalla; Chudasama, Mahesh Narbheram (Annals of Pathology and Laboratory Medicine, 2022)
Background: Infertility is of global health concern affecting one out of six couples worldwide, and Africa has reported the highest rates. Bacterial semen infections are considered to be one of the significant causes of infertility. Effective antimicrobial therapy is therefore essential in treatment of bacteriospermia. This study aimed to identify the bacterial pathogens present in semen and involved performing the antimicrobial susceptibility testing to improve the clinical management by identifying the antimicrobials that can be the best treatment option. Methods: Ninety semen specimens were collected from male patients having primary infertility who attended the clinic. Semen was cultured on Nutrient agar, Blood agar, MacConkey agar and Chocolate blood agar using standard bacteriological techniques. Bacterial isolates identification was done by studying the colony characteristics, performing gram staining reactions and biochemical testing. Modified Kirby-Bauer method was used in performing the antimicrobial susceptibility testing. Result: 51 (56.67%) patients presented with bacteriospermia. Staphylococcus aureus (29.41%) was the most common bacteria isolated, followed by Escherichia coli (23.53%), Coagulase negative staphylococcus species (17.65%), Klebsiella pneumoniae (11.76%), Proteus. mirabilis (7.84%), Pseudomonas. aeruginosa (5.88%) and Neisseria gonorrhoeae (3.92%). Most of the bacteria isolated were highly sensitive to ciprofloxacin, cefotaxime and ofloxacin and moderately sensitive to amikacin, gentamycin and cefuroxime. Conclusion: Bacteriospermia prevalence rate was 56.67% and was commonly observed in the age group of 30 - 39 years. Staphylococcus aureus was found to be the predominant causative agent of semen infection. The most effective antimicrobials were ciprofloxacin, cefotaxime and ofloxacin and the antimicrobial with least activity was co-trimoxazole.